PENGARUH EDUKASI BREASTFEEDING IBU POST PARTUM TERHADAP BREASFEEDING SELF EFFICACY - Riyanti, Eka; Nurlaila, Nurlaila; Astutiningrum, Diah (LPPM STIKES MUHAMMADIYAH GOMBONG, 2018)
The Baby must receive exclusive breastfeeding at the first six months of development from birth. Exclusive breastfeeding is still bellow of the target. Nutrition is important for baby’s survival, growth, and development. Mother's knowledge about exclusive breastfeeding take effect on exclusive breastfeeding. Knowledge and trust of the mother about breastfeeding can be enhanced by health education. This research to analyze the effect of breastfeeding education onpost-partum mothers regarding breastfeeding self-efficacy in RSUD Soedirman Kebumen. This Method is quasi-experiment design with one group pre-test and post-test design. Purposive sampling applied, as much 43 respondents joined in this study. Breastfeeding education has a significant effect on increasing self-efficacy atbreastfeeding mothers with P value = 0.00.The conclusion is breastfeeding education must be given to post-partum mothers in order to the belief breastfeeding of mothers increases.